The Refoundation of the Universitary Socialist Association during transition, 1977-1986 - Mateos, Abdón (CIAN-Revista de Historia de las Universidades, 2018)
In 1977, the Socialist University Association (ASU) was refounded as a section of the Socialist Federation of Madrid of the PSOE. Unlike the first ASU (1956-1961), the new Madrid socialist university students, coming from the working middle classes, had a social-democratic ideological profile rather than radical socialism. Throughout the first socialist legislature and with the crisis of NATO, ASU was losing the character of student group to increase its implementation among professors and become a recruitment section of socialist cadres.